KITOSAN DARI JAMUR TIRAM (Pleurotus ostreatus) DAN APLIKASINYA SEBAGAI ADSORBEN LOGAM KROM (Cr) - Dhini Annisa Rahmasari Kanto; Riza Apriani; Mira Ilhami; Ai Eva (UIN AR-RANIRY, 2021)
Oyster mushroom is one of the organisms that can be used as a chitosan source. Chitosan can be produced from chitin through deacetylation. As a chitin derivative compound, chitosan has immense application. In this study, chitin and chitosan were isolated from oyster mushrooms as much as 1.696% and 0.174% from 500 g of dried mushroom. The degree of deacetylation of chitosan is 80.70%. As a polycationic polymer, one of its applications is a metal adsorbent. Cr metal is a heavy metal that is mostly found in leather industrial waste. Chitosan is used as a Cr metal adsorbent to reduce Cr metal content in the solution. This study showed that there was a reduction of Cr metal content as much as 82.75%. Thus, chitosan isolated from oyster mushrooms in this study has the potential to be a bio-adsorbent in order to reduce Cr metal content in leather industrial waste.